2001
DOI: 10.1002/bdd.280
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and tissue distribution of the anticholinergics tiotropium and ipratropium in the rat and dog

Abstract: Ipratropium, a current treatment for chronic obstructive pulmonary disease (COPD) and tiotropium, a longer acting anticholinergic bronchodilator currently being developed for COPD are structurally related to atropine. In this study, the intravenous (i.v.), oral (p.o.) and intratracheal (i.tr.) single dose pharmacokinetics (PK) of tiotropium and ipratropium were determined in rat and dog. In rats, concentration-time profiles of tiotropium and ipratropium after single i.v. bolus administration of 7-8 mg kg(-1) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…It is notable, however, that there was no deterioration in subjective sleep quality as was seen in patients receiving high doses of long-acting inhaled b-agonists in one report [32]. A direct central nervous system effect of tiotropium on sleep quality is made less likely by the fact that studies in rats have shown that the drug does not penetrate the bloodbrain barrier to any relevant extent [33].…”
Section: Discussionmentioning
confidence: 95%
“…It is notable, however, that there was no deterioration in subjective sleep quality as was seen in patients receiving high doses of long-acting inhaled b-agonists in one report [32]. A direct central nervous system effect of tiotropium on sleep quality is made less likely by the fact that studies in rats have shown that the drug does not penetrate the bloodbrain barrier to any relevant extent [33].…”
Section: Discussionmentioning
confidence: 95%
“…After intravenous administration of [ 14 C]tiotropium to rats, the highest concentrations of radioactivity were detected in kidney and liver within a short period (Leusch et al, 2001). In rat liver, rOct1 is located to the sinusoidal membrane of hepatocytes (Meyer-Wentrup et al, 1998), but rOct2 is not expressed in liver (Okuda et al, 1996).…”
Section: Discussionmentioning
confidence: 98%
“…Although the origin of drug levels in the SMG is not completely understood, it is likely to be from systemic drug levels as opposed to local deposition of the aerosol, since rats are obligate nose breathers and will breathe from the mouth only when the nose is completely blocked (Schulz and Muhle, 2000). Thus, although one cannot completely rule out that some proportion of the drug may be delivered to the SMG via a local rather than systemic route, a plausible mechanism for the greater increase in tiotropium concentration in the SMG is through systemic exposure driven by its pharmacokinetic properties, which includes high bioavailability following local administration to the lung, large volume of distribution (Leusch et al, 2001), and a long terminal half-life (tiotropium NDA-21-395, 2003), all of which could lead to preferential distribution to the SMG. Taken together, these data confirm that the pharmacodynamic readouts of bronchoprotection and antisialagogue effects correlate well with concentrations of the compounds in the respective target tissues, and that the greater pharmacodynamic lung selectivity of TD-4208 is in line with this pharmacokinetic-pharmacodynamic relationship.…”
Section: Pharmacology Of Lung-selective Muscarinic Antagonist Td-4208mentioning
confidence: 99%